1999
DOI: 10.1046/j.1365-3040.1999.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet‐B‐induced stress and changes in gene expression in Arabidopsis thaliana: role of signalling pathways controlled by jasmonic acid, ethylene and reactive oxygen species

Abstract: Treatment with supplementary UV‐B resulted in decreases in transcripts of the photosynthetic genes Lhcb and psbA and concomitant increase in transcripts of two pathogen‐related genes, PR‐1 and PDF1·2, in Arabidopsis thaliana. UV‐B exposure caused increases in jasmonic acid (JA) levels and ethylene production. UV‐B treatment of jar1 and etr1‐1 mutants, which are insensitive to JA and ethylene, respectively, showed that the increase in PR‐1 transcripts was dependent on ethylene and PDF1·2 transcripts on both JA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
139
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(153 citation statements)
references
References 67 publications
12
139
0
2
Order By: Relevance
“…The induction of both H 2 O 2 and PDF1.2 by AtPep1 was blocked by first supplying the leaves with diphenylene iodominium chloride (DPI) (Fig. 3 C and D), an inhibitor of NADPH oxidase in both plant and animal tissues (20,29). The cumulative results indicated that AtPep1 requires H 2 O 2 for the transcription of PDF1.2, consistent with recently proposed pathways for JA͞ethylene signaling (28).…”
Section: Resultssupporting
confidence: 81%
“…The induction of both H 2 O 2 and PDF1.2 by AtPep1 was blocked by first supplying the leaves with diphenylene iodominium chloride (DPI) (Fig. 3 C and D), an inhibitor of NADPH oxidase in both plant and animal tissues (20,29). The cumulative results indicated that AtPep1 requires H 2 O 2 for the transcription of PDF1.2, consistent with recently proposed pathways for JA͞ethylene signaling (28).…”
Section: Resultssupporting
confidence: 81%
“…Those authors (Shin et al, 2005;Torabi et al, 2009) found the severity of P i deficiency directly correlated with the severity of the oxidative stress. Increased oxidative stress and ROS accumulation are known photosynthesis inhibitors (Mackerness et al, 1999). The majority of transcripts down-regulated in leaves due to P i deficiency ( Fig.…”
Section: Oxidative Stress Responsementioning
confidence: 99%
“…This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C. systemin show striking similarities to UV-B signaling, including proton and potassium fluxes (25)(26)(27), increases in intracellular Ca 2ϩ concentrations (28 -30), activation of calmodulin genes (28,31,32), activation of MAPKs (15,22,33,34), activation of an NADPH-dependent oxidase (35)(36)(37), generation of reactive oxygen species (11,25,35,38), and increases in levels of ethylene (27,39,40), and jasmonic acid (39,41,42). However, it is still largely unknown how these signaling events are initiated by UV-B, what their precise cellular function is, and whether wounding/systemin-induced pathways and UV-B-induced pathways utilize some common signaling components.…”
mentioning
confidence: 99%